THE EFFECT OF PROVIDING DASH DIET EDUCATION ON THE LEVEL OF KNOWLEDGE OF THE ELDERLY - Luthfiyyah Khanuun (CV. Fahr Publishing, 2026)
Hypertension is a major health problem in the elderly that requires long-term management, including through non-pharmacological approaches such as dietary adjustments. Dietary Approaches to Stop Hypertension (DASH) is a diet pattern proven effective in helping control blood pressure. However, the implementation of the DASH Diet in the elderly is greatly influenced by the level of knowledge. This study aims to determine the effect of providing DASH Diet education on the level of knowledge of the elderly. This study used a quasi-experimental design with a one-group pretest–posttest approach. The study sample consisted of 20 elderly people selected using a purposive sampling technique. The research instrument used was a DASH Diet knowledge questionnaire. Respondents were given DASH Diet education through a structured leaflet. Knowledge levels were measured before and after the education was provided. Data analysis was performed using the Wilcoxon signed rank test to determine differences in knowledge levels before and after the intervention with a significance level of 0.05. The results showed an increase in the level of knowledge of the elderly after being given DASH Diet education, with a p-value of 0.001 (p <0.05). This indicates that providing DASH Diet education has a significant effect on the level of knowledge of the elderly. The conclusion of this study is that DASH Diet education is effective in increasing the knowledge of the elderly and can be used as a promotive and preventive nursing intervention in managing hypertension in the elderly.